PERENCANAAN JALAN INSPEKSI DENGAN LAPIS PERMUKAAN PAVING BLOCK MODIFIKASI LIMBAH FLY ASH DI BANDAR UDARA HUSEIN SASTRANEGARA BANDUNG - Indah Tunjung Prabasar; Nurhedhi Desryanto; Ajeng Miranti P (Langit Biru: Jurnal Ilmiah Aviasi, 2019)
Husein Sastranegara Bandung airport currently does not have road inspection facility. Therefore, it is necessary to have such facility as an infrastructure to support monitoring activities at the airport. It is planned that the inspection road will use inspection pavement using flexible pavement with a surface layer, that is paving blocks using fly ash as a replacement for PC cement. The calculation analysis used is SNI 03- 1732-1989 F and Highway Geometric Design Procedures. From the calculation, the total thickness of the pavement is 31 cm with the subbase course 13 cm, base 10 cm, surface 8 cm. the width of the bend pavement is 2.55 m for all bend designs, while the inspection road dimension is 1,649 m in length with 5 m width. Thus, it is necessary to re-test the compressive strength of the pavement to get more maximum result